2019
DOI: 10.31846/jae.v4i2.155
|View full text |Cite
|
Sign up to set email alerts
|

Pengaruh Kompensasi Dan Pengembangan Karir Terhadap Kinerja Karyawan

Abstract: The purpose of this research is to examine the influence of compesantion and career development on employees performance . The first hypothesis examine wheter compensation influences performance.The second hypothesis examine wheter career development influences performance.The population in this researchare all employees at PT. FIF Group in Pasamam. This research uses by using technique of full sampling. Data were collected using a survey method and analyzed with doubled linear regression.The result of hypoth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
8
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 0 publications
3
8
0
3
Order By: Relevance
“…Sejalan dengan itu, pengembangan karir dianggap sebagai upaya internal organisasi untuk merencanakan karir pegawai yang meliputi perencanaan, pelaksanaan dan pengawasan pekerjaan yang disebut dengan manajemen karir 25 . Sistem pengembangan karir yang baik dapat mempromosikan kepuasan kerja karyawan yang pada akhirnya dapat membawa karyawan pada kinerja terbaik mereka 26 .…”
Section: Pengembangan Karir (Career Development)unclassified
See 1 more Smart Citation
“…Sejalan dengan itu, pengembangan karir dianggap sebagai upaya internal organisasi untuk merencanakan karir pegawai yang meliputi perencanaan, pelaksanaan dan pengawasan pekerjaan yang disebut dengan manajemen karir 25 . Sistem pengembangan karir yang baik dapat mempromosikan kepuasan kerja karyawan yang pada akhirnya dapat membawa karyawan pada kinerja terbaik mereka 26 .…”
Section: Pengembangan Karir (Career Development)unclassified
“…tempat mereka bekerja memiliki pengembangan karir yang jelas dan transparan 7 . Pengembangan karir (career development) karyawan dikatakan sebagai tindakan kepegawaian yang diarahkan untuk membantu karyawan dalam merencanakan karir masa depan mereka di perusahaan tempat mereka bekerja saat ini 8 . Karyawan yang diberikan kesempatan untuk mengembangkan karir secara keseluruhan dapat berkembang menuju potensi terbaik mereka.…”
unclassified
“…Correspondingly, the high level of salary is inconsonant with Lee et al (2017) found that salary has an impact on employee performance. Moreover, Endarwita, E. et al (2019) salary is given to employees which encourages them to exert maximum effort and enhances the organizations' success. A competitive compensation is highly regarded as employee welfare benefit that increase their performance and productivity in working for their company.…”
Section: Level Of Employee Performancementioning
confidence: 99%
“…Therefore companies should pay attention to such compensation. By providing an appropriate salary or more certainly will greatly affect the performance of the employee (18).…”
Section: The Effect Of Compensation On the Performance Of Medical Per...mentioning
confidence: 99%